Uncovering the universals of ubuntu translanguaging in classroom discourses. Issue 3 (2nd October 2019) - Makalela, Leketi
ABSTRACT: Increasing international mobility has raised awareness on the fluidity and porous nature of boundaries not only between nation states, but also between named languages. Despite the complexities of overlaps across a wider spectrum of languages and classrooms worldwide, orthodox education programmes still reflect monolingual and epistemic biases, which disproportionately put the majority of the students at an educational disadvantage. In this paper, I explore classroom data from African classrooms on how translanguaging is effective in deepening comprehension and cultivating a high sense of self. Samples of data from a primary school were analyzed to explain the nature and prevalence of translanguaging in South African classrooms. The results of the study show that there is a high prevalence of translanguaging that reflects infinite relations of dependency between various linguistic resources employed in classroom discourses. This multilingual usage is interpreted within the African value system of ubuntu (I x We): I am because you are . I then argue that this cultural competence can be leveraged for successful learning and teaching. In the end, I consider recommendations on how the universals of Ubuntu translanguaging as a regime for multilingual practices becomes transformative in enhancing epistemic access and identity positions of multilingual students.